Conversion of polypropylene to two‐dimensional graphene, one‐dimensional carbon nano tubes and zero‐dimensional C‐dots, all exhibiting typical sp2‐hexagonal carbon rings. Issue 1 (1st January 2015) - Sharon, Madhuri; Mishra, Neeraj; Patil, Bhushan; Mewada, Ashmi; Gurung, Raju; Sharon, Maheshwar
Abstract : For the first time single precursor, polypropylene (PP) has been used to synthesise two‐dimensional (2D) graphene, 1D carbon nanotubes (CNT) and 0D carbon dots (C‐dots). The carbon chains of PP polymer contain tertiary carbon atoms that have considerably lower resistance against degradation and cracking which is easy at low activation energy. Thermal cracking of PP was used for the synthesis of 2D graphene, 1D CNT and 0D C‐dots materials. Although the basic structure of all three materials is same, that is, having hexagonal lattice of carbon, they show different properties. Morphology of these carbon materials was characterised by scanning electron microscopy, transmission electron microscopy and properties along with sp 2 and sp 3 content were analysed by ultra‐violet–visible spectroscopy, X‐ray diffraction (XRD) and Raman spectroscopy. It was observed with the help of Raman and XRD that as the dimensionalities of hexagonal carbon decreases there is an increase in defects, for example, graphene synthesised from PP showed negligible defects, CNT had considerable disorderness, whereas 0D C‐dots showed maximum disorderness. This could be the reason for scientists turning from CNT to graphene as future material for its application in electrical and electronic fields, nevertheless, only time will tell whether graphene can be the answer as currently being thought of.